The Contribution of Linguistics Knowledge to the Field of English Language Teaching - Santa Maya Pramusita; Eni Kustanti; Betty Sianturi (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
This paper attempts to examine the correlation among linguistics and English language teaching in non-english speaking countries. Since it is a library research, the researchers gathered the information by using secondary sources. This paper generally consists of three parts. The first part defines general review of linguistics and language teaching. In general review of linguistics, the researchers describe the elements of linguistics, whereas in language teaching review, the skills of language are elaborated. The second part is about the historical connection between linguistics and language teaching. Menwhile, the last part discusses about the contribution of linguistics theories elements, and branches to language teaching. The result of this research discovers that linguistics theory, elements, and branches have an immense contribution to language teaching, and becomes an indispensable part of language learning.